Preparation and Characterization of Alkaline and Acidic Heterogeneous Carbon-Based Catalysts and Their Application in Vegetable Oil Transesterification to Obtain Biodiesel. (20th July 2022) - Díaz-Muñoz, L. L.; Reynel-Ávila, H. E.; Mendoza-Castillo, D. I.; Bonilla-Petriciolet, A.; Jáuregui-Rincón, J.
Abstract : This paper reports the preparation, evaluation, and comparison of alkaline and acidic heterogeneous carbon-based catalysts in the transesterification of safflower oil with methanol to obtain biodiesel. These catalysts were obtained from the pyrolysis of flamboyant pods and their functionalization and activation with potassium hydroxide, citric acid, tartaric acid, sulfuric acid, and calcium nitrate. Different routes for the preparation of these catalysts were tested and analyzed where the FAME formation was the target variable to be improved. Results showed that the catalyst prepared with potassium hydroxide and calcium nitrate achieved the highest FAME formation (i.e., 95%) and outperformed the catalysts prepared with calcium nitrate and other acids even after four regeneration-reaction cycles. The best properties of an alkaline catalyst could be associated with its specific surface area and contents of potassium and calcium moieties, which were higher than those observed for acidic catalysts. Transesterification rates for biodiesel production were better estimated with the pseudo-order kinetic model, which ranged from 0.0004 to 0.038 L/mol⋅min for alkaline and acidic catalysts.